Topological structure of simple pro-Hamiltonian flows on the Möbius strip - Prishlyak, O.; Stas’, S. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 515.1We investigate the topological properties of flows on the Möbius strip, whose lift to a double cover, which is a cylinder, consists of Hamiltonian flows with a Hamiltonian that is a Morse function, constant on the boundary components. We construct a topological classification of such simple flows using distinguishing graphs made up of rooted trees, which are Reeb graphs. The resulting recursive formula calculates the number of topologically non-equivalent flows with a given number of saddles.